Preliminary study of the facial hair follicle parasites / Nur Amirah Azian - Azian, Nur Amirah (Faculty of Applied Sciences, 2016)
Facial hair follicle parasites which is Demodex mites are found in the human hair follicles and normally found in greater number around the cheeks, nose, eyebrows, eyelashes and forehead. It is a species of tiny mites that lives in pores and hair follicles. The aim of this study is to identify and compare the parasites that lives on the human facial hair follicle by using two types of method which are Smoke and Traditional method. The samples of the facial hair follicle collected from the two methods was collected by using the forceps, soft brush and small sponge. The sample was preserved in the 70% alcohol. The sample have to be kept in the 70% alcohol so it will be last longer and not damage. The sample was then observed and identified by using microscopes. Dissection method was conducted to the Brown-Hooded Cockroach to confirm that the Nematode which protruded from the patient’s face which undergo the traditional method treatment is come from the cockroach and not from the patient’s skin. It was concluded that the facial hair follicle parasites is Demodex mites and it can be removed by using the Traditional method of treatment.